ANALISIS KEADILAN SUBSTANSIAL PADA PENERAPAN UNDANG-UNDANG PERLINDUNGAN DATA PRIBADI TERHADAP HAK PEMILIK DATA DALAM PERSPEKTIF HUKUM POSITIF DAN HUKUM ISLAM - Hanafi, Fauzan; Hi Talib, Abdul Balgis; Din, Musaddi (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2025)
This study aims to analyze the principle of substantial justice in its application within Indonesia’s Personal Data Protection Act (UUPDP) by comparing Indonesian positive law with Islamic law. The UUPDP was introduced to protect personal data owners, covering rights such as access, rectification, deletion, and the right to refuse data processing. The implementation of this law faces challenges that ultimately hinder comprehensive data protection. Privacy rights are also emphasized in Islamic law, alongside the right to fair treatment, which is a fundamental principle aimed at protecting individuals’ substantive rights. The findings of this study reveal that UUPDP implementation remains suboptimal, particularly in terms of law enforcement, affecting the effectiveness of substantial justice applications. Enhancing the effectiveness of the UUPDP can be achieved through robust law enforcement, improved infrastructure and human resources, and public education. By integrating Islamic law and positive law, a stronger ethical foundation and a broader landscape are provided for assessing, evaluating, and maximizing personal data protection. These recommendations include enhancing UUPDP implementation, strengthening dispute resolution mechanisms, and ensuring that the principle of substantial justice is fully and optimally applied in protecting the personal data of Indonesian citizens.